Comparative Analysis of Contract Prices with Basic Prices for Structural and Architectural Works (Case Study: Construction of The Jayapura III-19 Military Court Office Building) - Erwin, Erwin; Sinaga, Antas Haulian; Carlos, Adrian (West Science Interdisciplinary Studies, 2025)
This research aims to analyze the comparison between contract prices and basic prices for structural and architectural works in the construction project of the Military Court Office Building III-19 Jayapura. This comparison is essential to ensure budget efficiency and to prevent budget misuse through unreasonable mark-up practices. The research employs a quantitative approach and the cost-plus pricing method, with data obtained from field surveys (primary data) and project documentation (secondary data). The results indicate a price difference of 2.4% for structural work and 10.4% for architectural work between contract prices and basic prices. According to the fair profit analysis based on the Ministry of Public Works Regulation No. 1 of 2022, most of the works fall within the acceptable profit margin of 10–15%. This study is expected to serve as a reference for future planning and control of construction project budgets.